Shoplifting Behavior Among Patients With an Eating Disorder at a Medical Correctional Center in Japan: A Cross-Sectional Study - Miyamoto, Etsuko; Okumura, Yusuke; Maruo, Kazushi; Kitani, Seiichi (Frontiers in Psychiatry, 2022)
Purpose: In Japan, the incarceration of patients with eating disorders (EDs) owing to repeated shoplifting has become a social issue. This study examined the shoplifting behavior of inmates with EDs at our medical correctional center, with the objective of delineating their characteristics, identifying an adequate treatment plan, and preventing recidivism. Methods: The participants consisted of 32 incarcerated patients with EDs (22 females, 10 males) charged with shoplifting, from a medical correctional center in East Japan. A cross-sectional study was employed. Data were collected by retrieving the patients’ medical records and through individual interviews conducted by psychiatrists. Results: The food-specific shoplifting ED group (those who had never shoplifted anything other than food) had a core pathology of the binge-purge type of anorexia nervosa with juvenile onset (p = .044). Furthermore, they demonstrated an average gap of eight years between the onset of ED and their first shoplifting episode. The non-specific shoplifting ED group (those who shoplifted food and other items) typically shoplifted before the onset of ED (p = .001). They experienced the onset of ED after incarceration (p = .004) and had comorbid disorders (p = .024). The food-specific group required a psychosocial approach focusing on maintaining healthy body weight and mental stability, whereas the non-specific group required multiple forms of support for substance abuse and behavioral addiction, as well as interventions to reduce impulsive behavior. Conclusion: Early intervention is necessary to improve the prognosis of patients with EDs and shoplifting behavior.